Optimizing blood alcohol concentration measurement with breath alcohol meter and its preliminary application in evaluating CYP2E1 activity - Jiayi Zhang; Yingqi Hu; Ziqi Jin; Runa A; Xiaoxue Wang; Lingyu Zhang; Yongzhi Xue (PLoS ONE, 2025)
Background Ethanol metabolism in vivo is primarily mediated by CYP2E1 and alcohol dehydrogenase, with CYP2E1 playing the predominant role at high ethanol concentrations. However, it is a difficult problem to evaluate CYP2E1 activity with ethanol as a probe, especially in rats. Currently, high-performance liquid chromatography (HPLC)-based detection of chlorzoxazone is the standard method for evaluating CYP2E1 activity. Nevertheless, this method is labor-intensive, time-consuming, costly, and unsuitable for real-time on-site or multipoint noninvasive monitoring. Objectives This study aimed to develop and optimize a noninvasive and rapid method for blood alcohol concentration BAC detection in rats. The optimized approach was subsequently applied to preliminarily assess hepatic CYP2E1 activity. Methods Male Sprague-Dawley rats were randomly divided into two groups: the immune-mediated liver injury (hepatitis) group and the control group. Hepatitis rats was induced by tail vein injection of Bacillus Calmette-Guerin and lipopolysaccharide, whereas the control rats received an equivalent volume of normal saline. On day 14 of the experiment, following intragastric administration of 56% (v/v) alcohol (5 mL·kg ⁻ ¹), BAC in both groups was measured using a breath alcohol meter. The BAC-time curve was segmented at 46 mg·dL ⁻ ¹: the upper portion was used to assess CYP2E1 activity, while the lower portion reflected alcohol dehydrogenase activity. Liver tissues were collected from rats and observed for histopathological changes using hematoxylin and eosin staining. To validate the accuracy of breath alcoholmeter, headspace gas chromatography was employed. Additionally, HPLC was used to determine plasma chlorzoxazone metabolism, serving as an independent measure of CYP2E1 activity. Based on these findings, we further investigated the potential of ethanol as a probe substrate for assessing the activity of CYP2E1. Results The pathological findings demonstrated that BCG successfully induced immune liver injury in rats. Comparative analysis using both breath alcohol meter and gas chromatography revealed significantly reduced alcohol metabolism in the immune-mediated liver injury rats relative to the control. The gas chromatographic measurements of BAC confirmed the accuracy and reproducibility of the breath alcohol detection method. Furthermore, HPLC analysis demonstrated a marked reduction in CYP2E1 activity in the liver injury rats compared to control. Conclusion The breath alcohol detection method offers a simple, non-invasive approach that can serve as a viable alternative for assessing hepatic CYP2E1 metabolic activity.